Antilock brake algorithm for heavy commercial road vehicles with delay compensation and chattering mitigation. Issue 4 (3rd April 2021) - Sridhar, Nithya; Devika, K. B.; Subramanian, Shankar C.; Vivekanandan, Gunasekaran; Sivaram, Sriram
Abstract : This work provides a model-based approach to develop a wheel slip regulation scheme for Antilock Braking System (ABS) in Heavy Commercial Road Vehicles (HCRVs). Physical constraints of the actuator in the pneumatic brake system such as operating bandwidth and delay were considered in the design. The slip regulation scheme was designed using Power Rate Exponential Reaching Law (PRERL) based Sliding Mode Controller (SMC), which is a new strategy employed for ABS application. This technique consists of both chattering mitigation and robustness properties. Additionally, the effect of actuator delay on performance deterioration of the slip regulator was studied and an appropriate method was developed to mitigate it. The complete design was evaluated in a Hardware-in-Loop (HiL) experimental setup for several cases of road and load conditions and seen to regulate slip fairly accurately with an average tracking error of 8.26 % . Further, the stopping distance reduction was up to 36 % with the controller. The developed algorithm was found to be robust to ± 40 % of mass variations and ± 15 % of road surface variations.